2021
DOI: 10.13005/bpj/2231
|View full text |Cite
|
Sign up to set email alerts
|

Assisted Reproductive Technologies for Women with Polycystic Ovarian Syndrome

Abstract: Polycystic ovarian syndrome (PCOS) is the most common cause of anovulatory fertility problems in women of reproductive age, with a prevalence as high as 40% to 75%. There are different treatment modalities for increasing the chance of pregnancy in PCOS patients. Since most of the PCOS patients suffer from ovulatory problems, therapeutic efforts are focused mainly towards restoring normal ovulation. However, even after pharmacological interventions to ameliorate ovulatory irregularities, women with polycystic o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…These immature follicles become the emblematic tiny cysts observed via ultrasonography, providing the ovaries their 'polycystic' nomenclature. 5,16…”
Section: Ovulatory Disturbancesmentioning
confidence: 99%
See 1 more Smart Citation
“…These immature follicles become the emblematic tiny cysts observed via ultrasonography, providing the ovaries their 'polycystic' nomenclature. 5,16…”
Section: Ovulatory Disturbancesmentioning
confidence: 99%
“…71 Notably, OS stands out as a crucial factor that intensifies the reproductive abnormalities in PCOS. 6,16,72 Studies have shown that the ovaries of individuals with PCOS exhibit increased generation of ROS. 67 Under normal conditions, ROS are counteracted by antioxidant defenses to ensure cellular equilibrium.…”
Section: Infertility and Reproductive Issuesmentioning
confidence: 99%
“… 7 It has been suggested that oocytes retrieved from polycystic ovaries have an abnormal zone pellucida structure, which can lead to decreased fertilization rates; therefore, intracytoplasmic sperm injection (ICSI) may increase fertilization rates in eggs retrieved from women with PCOS. 8 …”
Section: Ovulatory Disordersmentioning
confidence: 99%
“…The disease is mainly characterized by an excess availability of androgen and ovarian dysfunctions [4]. Several research articles indicate that PCOS is the most common endocrine and metabolic disorder in women of reproductive age [5][6][7]. The presence of any two of the conditions, i.e., the presence of oligo or anovulation, clinical or biochemical androgen excess or polycystic ovarian morphology detected by ultrasonography can be used as an identifying tool for the diagnosis of PCOS [8].…”
Section: Introductionmentioning
confidence: 99%